Ferrofluid Microdroplet Splitting for Population‐Based Microfluidics and Interfacial Tensiometry - Mika Latikka; Matilda Backholm; Avijit Baidya; Alberto Ballesio; Amandine Serve; Grégory Beaune; Jaakko V. I. Timonen; Thalappil Pradeep; Robin H. A. Ras (Advanced Science, 2020)
Abstract Ferrofluids exhibit a unique combination of liquid properties and strong magnetic response, which leads to a rich variety of interesting functional properties. Here, the magnetic‐field‐induced splitting of ferrofluid droplets immersed in an immiscible liquid is presented, and related fascinating dynamics and applications are discussed. A magnetic field created by a permanent magnet induces instability on a mother droplet, which divides into two daughter droplets in less than 0.1 s. During the splitting process, the droplet undergoes a Plateau–Rayleigh‐like instability, which is investigated using high‐speed imaging. The dynamics of the resulting satellite droplet formation is shown to depend on the roughness of the supporting surface. Further increasing the field results in additional splitting events and self‐assembly of microdroplet populations, which can be magnetically actuated. The effects of magnetization and interfacial tension are systematically investigated by varying magnetic nanoparticles and surfactant concentrations, and a variety of outcomes from labyrinthine patterns to discrete droplets are observed. As the splitting process depends on interfacial tension, the droplet splitting can be used as a measure for interfacial tension as low as 0.1 mN m−1. Finally, a population‐based digital microfluidics concept based on the self‐assembled microdroplets is presented.